Pengaruh Penggunaan Model Project Based Learning Terhadap Keterampilan Kolaborasi Mahasiswa Pendidikan IPA - Sitti Saenab; Sitti Rahma Yunus; Husain Husain (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
This report aims to review the influence of the use of learning model learning project based on skill collaboration education students science education UNM. The research is praeksperimen research. A design study used is one- shot case study. Subjects research is a student science education that doing lecture motion and change. Research instruments used to measure skill collaboration students is the instrument non the tests which consisted of rubric and the survey. Analysis of data done through descriptive statistics and statistics inferential. Analysis deskriktif statistics show that increased skill collaboration students when dibelajarkan use the model project is based learning about 18 of 29 students able to reach the score over the level of 1. While to test inferential shows that is the kind of classroom learning project based on skill collaboration Key Words: PjBL, Skill Colobaration, Science Education